Pelaksanaan Pembelajaran Literasi di SMP Negeri 1 Jember Tahun 2019 - Isnaniatul Lailiyah (heritage, 2021)
Literacy learning is an activity, a program implemented by schools to train students to have extensive reading, insight, and information about many things. This is doing by students in other to have critical thinking about what they have read. On the other hand literacy learning is done not only by reading, but also by writing. Reading and writing become a unity in the implementation of literacy learning. The purpose of this study is to describe the implementation of reading literacy learning in SMP Negeri 1 Jember and describe the implementation of cultural and citizenship literacy learning at SMP Negeri 1 Jember. This study uses a qualitative approach and descriptive research type. The location of this research is in SMP Negeri 1 Jember. Determination of informants using purposive techniques. Data collection techniques with interviews, observation and documentation. Data analysis uses the interactive model of Miles, Huberman and Saldana. The validity of the data uses technical triangulation and source triangulation. The results of this study indicate the implementation of reading literacy learning is carried out with several activities, namely learning to read silent reading literacy, reading literacy 4 books every 1 semester, learning literacy reading with a mandatory library visit day system, learning literacy reading outside the classroom, and making reading corners and implementing learning cultural and citizenship literacy is carried out with several activities, namely the implementation of literacy presentations, class mading competitions, literacy competitions to write poems on the Heroes' Day and Youth Pledge, cultural literacy exhibitions, and book fairs.